A Smartphone App for Improvement of Colonoscopy Preparation (ColoprAPP): Development and Feasibility Study - Walter, Benjamin; Schmid, Roland; von Delius, Stefan (JMIR Publications, 2017)
BackgroundOptimal bowel preparation is one of the major cornerstones for quality of colonoscopy. But poor bowel preparation still occurs in 10% to 25% of all patients. To optimize patient guidance, we developed a new smartphone app (ColoprAPP) for Android smartphones which guides and accompanies the patient starting 4 days before colonoscopy throughout the whole colonoscopy preparation procedure. ObjectiveThe objective of this study was to assess the function of a newly developed smartphone app for supporting colonoscopy preparation. MethodsWe carried out a prospective feasibility study including 25 patients undergoing outpatient colonoscopy at our hospital. As a control, we retrieved the data of 25 patients undergoing outpatient colonoscopy matching in age, sex, and indication for colonoscopy from our colonoscopy database. Patients were asked to download the smartphone app, ColoprAPP, in addition to being given the regular colonoscopy preparation leaflet. All colonoscopies were performed in the morning after using a split-dose preparation containing a polyethlene glycol-based purgative. The study was designed to test feasibility of the prototype, evaluate grade of bowel cleanliness (Boston bowel preparation scale [BBPS]), and assess patient satisfaction with the app. ResultsThe smartphone app use was feasible in all patients. BBPS count as a marker for grade of bowel preparation was significantly higher in the smartphone app-supported group (mean 8.1 [SD 0.3] vs 7.1 [SD 0.4], P=.02). Left (mean 2.8 [SD 0.1] vs 2.4 [SD 0.11], P=.02) and transverse colon (mean 2.8 [SD 0.07] vs 2.4 [SD 0.11], P<.001) revealed significantly higher BBPS counts in the smartphone app-supported group than in controls. Patient satisfaction with a smartphone app-supported colonoscopy preparation was high with an average numeric rating scale score for usefulness of 8.2 (visual analog scale 1-10). ConclusionsA novel developed smartphone app for reinforced education of bowel cleansing was feasible and led to high BBPS scores and patient satisfaction. Trial registrationClinicalTrials.gov NCT02512328; https://clinicaltrials.gov/ct2/show/NCT02512328 (Archived by WebCite at http://www.webcitation.org/6sz3Kk26z)